1999
DOI: 10.1002/(sici)1097-0290(19991205)65:5<491::aid-bit1>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Multisubstrate biodegradation kinetics of naphthalene, phenanthrene, and pyrene mixtures

Abstract: Biodegradation kinetics of naphthalene, phenanthrene and pyrene were studied in sole‐substrate systems, and in binary and ternary mixtures to examine substrate interactions. The experiments were conducted in aerobic batch aqueous systems inoculated with a mixed culture that had been isolated from soils contaminated with polycyclic aromatic hydrocarbons (PAHs). Monod kinetic parameters and yield coefficients for the individual compounds were estimated from substrate depletion and CO2 evolution rate data in sole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
2
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 23 publications
4
79
2
3
Order By: Relevance
“…Although these kinetics can in some cases be described by relatively simple no-interaction (16) or competitive inhibition (9,18,20) models, we have demonstrated that such models are inadequate for P. putida F1 growing on mixtures of toluene, benzene, and phenol and for Burkholderia sp. JS150 growing on mixtures of toluene and phenol.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although these kinetics can in some cases be described by relatively simple no-interaction (16) or competitive inhibition (9,18,20) models, we have demonstrated that such models are inadequate for P. putida F1 growing on mixtures of toluene, benzene, and phenol and for Burkholderia sp. JS150 growing on mixtures of toluene and phenol.…”
Section: Discussionmentioning
confidence: 93%
“…More recently, models have been proposed and tested for larger mixtures. Examples include the growth of Escherichia coli on six sugars (16), the growth of a mixed culture on benzene, toluene, ethylbenzene, and o-and p-xylene (BTEX compounds) (11), and the biodegradation of three polycyclic aromatic hydrocarbons (20).…”
mentioning
confidence: 99%
“…The specific affinity (calculated as maximum degradation rate [V max ]/Michaelis-Menten half-saturation constant [K m ]) of LB501T cells for aqueous anthracene was found to be higher than the specific affinities of other cultures reported elsewhere (41). A diverse range of K m values for PAH degradation have been obtained with pure cultures (1,12,18,27,36) and mixed cultures (19). Wick et al have proposed the presence of a high-affinity uptake system in LB501T (41), which would account for the facile degradation of aqueous-phase PAHs occurring at extremely low concentrations in the environment.…”
mentioning
confidence: 99%
“…In the presence of surfactant, Boonchan et al (2000) found that Stenotrophomonas maltophilia VUN 1,0010s degraded mixtures of PAHs faster in the presence of surfactant than in the absence of surfactant, and the maximum specific degradation rate of each component from the mixture was smaller than when it was degraded alone. Similar decreases in the degradation rate of individual PAHs due to the presence of other PAHs have been found in the absence of surfactants for mixed cultures (Guha et al, 1999) and for pseudomonads (Stringfellow and Aitken, 1995a;Bouchez et al, 1995). Further work in this area is necessary to provide a greater understanding of how surfactants influence the microbial degradation of mixtures and to make the application of surfactants a standard engineering tool in biological soil remediation (Volkering et al, 1998).…”
Section: Microbiological Studiesmentioning
confidence: 78%